The value of fixed segment mobility in posterior dynamic stabilization: a single-center retrospective study - Yulu Sun; Jianbin Guan; Hao Chen; Xiaojie Sun; Kaitan Yang; Qing Fang (BMC Musculoskeletal Disorders)
Abstract Purpose This study aims to compare the effects of two generations of the Isobar dynamic fixation system—Isobar TTL (first-generation, less mobile) and Isobar EVO (second-generation, more mobile)—on the surgical and adjacent intervertebral disc segments, based on MRI findings. Methods A retrospective analysis was conducted on 29 patients treated with fenestrated decompression and Isobar EVO stabilization and 34 patients treated with fenestrated decompression and Isobar TTL stabilization. Clinical outcomes and radiographic parameters, including the disc height index (DHI) and range of motion (ROM) of the surgical and upper adjacent segments, lateral neural foraminal protrusion value (LNPV) of the upper adjacent segment, and Pfirrmann grading of disc degeneration, were evaluated and compared between the two groups. Results At the 48-month follow-up, no significant differences in Visual Analog Scale (VAS) scores or Oswestry Disability Index (ODI) were observed between the two groups (P > 0.01). The EVO group demonstrated significantly higher surgical segment DHI and ROM compared to the TTL group (P < 0.01). Meanwhile, the upper adjacent segment ROM was significantly lower in the EVO group compared to the TTL group at the final follow-up (P < 0.01). Additionally, the upper adjacent segment LNPV was larger in the EVO group than in the TTL group (P < 0.01). Pfirrmann grading revealed greater degeneration in surgical segments treated with TTL compared to EVO (P = 0.008). Conclusion Compared to the first-generation, less mobile Isobar TTL, the second-generation, more mobile Isobar EVO offers superior preservation of the surgical segment and slows the progression of degeneration in the upper adjacent segments. These findings highlight the benefits of greater mobility in posterior dynamic stabilization devices.